A Digital self-management blood glucose tracker - Nur Fariha, Razali; Azma, Abdullah (2021)
The rate of diabetes mellitus in Malaysia is one of the highest worldwide. Mobile health (mHealth) has become a conventional mode for delivering health services around the world. In term of self-management, mHealth becomes a crucial to keep on track and achieve good health.